2015
DOI: 10.1108/srj-02-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility, environmental leadership and financial performance

Abstract: In this study we statistically assess the relationship between corporate characteristics, environmental contribution, and financial performance. To this end, we compare the financial performance of all US corporations that have composed the Dow Jones Sustainability Indexs (DJSI), being the most proactive companies in providing services and goods while maintaining ethical responsibility and environmental sustainability. Performance is compared to mean performance of the related industry, sector, and the market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 46 publications
4
63
1
10
Order By: Relevance
“…Many of the authors chose not to establish a proper method of measuring the environmental aspect of sustainability by comparing companies belonging to sustainability/social responsibility indices to their counterparts (Adegbite et al, ; DiSegni et al, ; Lee et al, ), analyzing the act of environmental disclosure and its effects on financial performance (Said et al, ), and possessing an environmental friendly certification (Krause, ). There is, however, a great variety of variables which were created to measure environmental performance specifically.…”
Section: Implications For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the authors chose not to establish a proper method of measuring the environmental aspect of sustainability by comparing companies belonging to sustainability/social responsibility indices to their counterparts (Adegbite et al, ; DiSegni et al, ; Lee et al, ), analyzing the act of environmental disclosure and its effects on financial performance (Said et al, ), and possessing an environmental friendly certification (Krause, ). There is, however, a great variety of variables which were created to measure environmental performance specifically.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…ROA ratio represents the relative profitability of asset utilization and measures managerial efficiency [10,72,73]. In this way we intend to evaluate the effect of ROA, along with other control conditions, on the relationship between social performance and ROE.…”
Section: Industry (Activity Sector)mentioning
confidence: 99%
“…During this era, CSR is an action tool of top management for long-term success, as described in earlier research by Gray, Owen and Adams (1996), since many corporate organisations believe that success with CSR strategies will lead to success in organisation performance too, as it constitutes a benefit not only to the society but to the business itself also (Ditlev-Simonsen & Midttun, 2011;DiSegni, Huly, & Akron, 2015). Hence, a larger number of companies are engaged in a serious effort to define and integrate CSR strategies into all aspects of their businesses due to the globalization (Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%